Non-Surgical Biliary Drainage on Biliary Obstruction due to Malignancy - Evy Yunihastuti; L A Lesmana; Ari Fahrial Syam; Irsan Hasan; Karmel Tambunan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2001)
Surgery is still the golden standard of curative therapy for malignant biliary obstruction, but only 10- 20% of cases considered resectable. Therefore, palliative therapy to relieve pain, cholestasis, and biliary obstruction, is the main treatment for most patients. The development of percutaneous transhepatic biliary drainage and endoscopic biliary drainage had brought about minimally invasive treatment for malignant biliary obstruction, which had lower morbidity and mortality than surgical drainage. The choice of drainage technique depends on type of tumor, site of obstruction, also the available expert and instrumentation.    Keywords: malignant  biliary  obstruction,  percutaneous  transhepatic  biliary  drainage, therapeutic endoscopic retrograde cholangiopancreatography